Two new Terfezia species from Southern Europe - Bordallo, Juan Julián; Rodríguez, Antonio; Kounas, Vasileios; Camello, Francisco; Honrubia, Mario; Morte, Asunción (Phytotaxa, 2015)
Two new species of Terfezia, Terfezia grisea and Terfezia cistophila, are documented from Spain and Greece, based on morphology and ITS-rDNA sequence data. Macro and micro descriptions with illustrations and ITS phylogenetic data for the two species are provided, which are discussed in relation to similar species in this genus and their host plants.